Protein quality of raw soybean (Glycine max.), vigna (Vigna unguiculata) and canavalia (Canavalia gladiata) meal in growing rats - Aguirre, L.A.; Savón, L.; Oramas, A.; Dihigo, L.E.; Rodríguez, V. (My University, 1998)
Thirty Sprague-Dawley rats from 45 to 50 g live weight and 21 days of age were used in a random block design (six rats per treatment) to evaluate the protein quality of three meals of raw legume grains: canavalia (Canavalia gladiata), soya bean (Glycine max) and vigna (Vigna unguiculata) in respect to casein and considering the albumin based diet as the control of endogen secretions. The quality indices evaluated were: biological value (%), true digestibility(%), net protein utilization (%), usable protein (%), protein efficiency rate and retained N in respect to N consumed. Performance traits were also determined: initial live weight (g), final live weight (g), consumption (g animal(-1) day(-1)), average daily gain (g animal(-1) day(-1)) and feed conversion and the absolute weights (g), in relation to live weight (g/g) and to metabolic weights (g/g(0.75)) of liver, pancreas, thymus and thyroid glands. No significant differences were found in animals consuming soya bean (biological value = 74.07, true digestibility = 82.93) in respect to the control. The animals consuming vigna (biological value = 57.05, true digestibility = 70.21) were significantly different (P < 0.001) although the results were satisfactory. Only the liver weight diminished (P < 0.001) due to the consumption of both meals. The results were lower with canavalia (biological value = 52.74, true digestibility = 61.65) with lower liver weights (P < 0.001), thymus (P < 0.01) and thyroide (P < 0.01). The protein quality of raw soya bean and vigna was adequate, but this did not hold true for canavalia, thus further studies with the two former meals and new methods to raise the quality of the latter are required.